Pengaruh Kadar Air Dan Jenis Plastisizer Terhadap Sifat Fisik Plastik Biodegradable Dari Campuran Pati Jagung Dan Polivinil Alkohol - Budi Utami; Hendartini Hendartini (Jurnal Kimia dan Kemasan, 2000)
Recently the use of plastic packaging is become avoided because their waste will create environmental problem. As an alternative choice the use of biodegradable plastic packaging has been developed Research on biodegradable plastic has been carried out to study the effect of water content and kind of plasticizer on mechanical properties of the biodegradable plastic made from corn starch and polyvinyl alcohol. The result shows that water can increase the elongation of the plastic, but on the other hand it can decrease the tensile strength and barrier properties by increasing the water vapour transsmision rate. Therefore the use of water as a plasticizer must be mixed with other plasticizer such as glycerol, sorbitol, polyethylene glycol and glycerol monostearate. In this study the best result is by using mixture of water and sorbitol with ratio = 5: I and the ratio of solid material (starch + PVOH +nucleating agent) and plasticizer = 1 : I.